Analisis Arsip Kolonial: Efektivitas Strategi Dakwah Tradisional dan Dinamika Kristenisasi di Mandailing pada Abad ke-19 - Muhammad Syafrizal (Jurnal Dakwah dan Masyarakat, 2026)
This study examines the effectiveness of traditional Islamic da’wah in Mandailing society and the dynamics of resistance toward Christian missionary activities in the nineteenth century through the analysis of Dutch colonial archives and local historical sources. The research employs a historical-qualitative approach supported by source criticism and comparative analysis. The theoretical framework integrates religious communication, message authority, diffusion of innovation, and cultural resistance. The findings reveal that the Mandailing da’wah system, grounded in the authority of Islamic scholars (tuan guru), the network of the Naqshbandi Order, the pedagogical tradition of surau, and the integration of Islam within the socio-cultural structure of dalihan na tolu, created a strong and multilayered religious communication system. This condition caused missionary initiatives, including schools, churches, and social programs, to face structural limitations due to their incompatibility with the established Islamic network. The study concludes that traditional da’wah functioned not only as a medium for disseminating Islamic teachings but also as a mechanism of cultural resilience that strengthened resistance against external religious penetration. This research contributes to studies of Indonesian Islam, religious colonialism, and religious communication in Southeast Asia. Penelitian ini mengkaji efektivitas dakwah tradisional masyarakat Mandailing serta dinamika resistensi terhadap misi Kristen pada abad ke-19 melalui analisis arsip kolonial Belanda dan sumber lokal. Penelitian menggunakan pendekatan historis-kualitatif dengan metode kritik sumber dan analisis komparatif. Kerangka teori yang digunakan meliputi komunikasi keagamaan, otoritas pesan, difusi inovasi, dan resistensi budaya. Hasil penelitian menunjukkan bahwa sistem dakwah Mandailing yang bertumpu pada otoritas ulama (tuan guru), jaringan Naqshbandi Order, tradisi pendidikan surau, serta integrasi Islam dalam struktur sosial dalihan na tolu membentuk sistem komunikasi keagamaan yang kuat dan berlapis. Kondisi tersebut menyebabkan program zending berupa sekolah, gereja, dan kegiatan sosial mengalami keterbatasan karena tidak kompatibel dengan jaringan dakwah yang telah mapan. Penelitian ini menegaskan bahwa dakwah tradisional tidak hanya berfungsi sebagai media penyebaran ajaran Islam, tetapi juga menjadi mekanisme ketahanan budaya yang membentuk resistensi masyarakat terhadap penetrasi keagamaan eksternal. Kajian ini berkontribusi pada studi Islam Nusantara, kolonialisme agama, dan komunikasi keagamaan di Asia Tenggara.